A lithium ion battery positive electrode sheet and preparation method thereof, and a lithium ion battery

By using polymer electrolyte and inorganic filler modified active material layers in the lithium-ion battery positive electrode sheet, the problem that existing lithium-ion battery positive electrode materials are difficult to take into account high circulation performance, thermal stability and production costs when increasing the energy density, and battery performance with higher energy density, higher circulation stability and higher safety are achieved.

CN119069640BActive Publication Date: 2025-03-14TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411554068.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

While improving the energy density, existing lithium-ion battery positive electrode materials are difficult to take into account high cycling performance, thermal stability, structural stability and production costs.

Method used

The polymer electrolyte and inorganic filler, especially the synthetic monomer of polymer electrolyte, contains a crosslinkable perfluoroalkyl ionic liquid for the modified active material layer by introducing polymer electrolytes into the positive electrode sheet of the lithium-ion battery.

Benefits of technology

It achieves higher energy density while taking into account high cycle stability, thermal stability and safety, reduces production costs, and improves the rate performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069640B_ABST
    Figure CN119069640B_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium-ion battery positive electrode sheet and a preparation method thereof, and a lithium-ion battery, which belongs to the field of lithium-ion batteries and solves at least one of the following problems existing in existing lithium-ion batteries: high-nickel positive electrode materials are difficult to take into account high cycle performance while improving energy density; high-nickel positive electrode materials have safety risks; high-nickel positive electrode materials have insufficient structural stability; production is difficult, the process flow is cumbersome, and expensive elements need to be introduced, resulting in a significant increase in cost. A lithium-ion battery positive electrode sheet includes a positive electrode collector and an active material layer disposed on the positive electrode collector and containing a modifier; the modifier includes a polymer electrolyte and an inorganic filler, and the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid. The positive electrode sheet and preparation method provided by the present invention can achieve high energy density while taking into account high cycle performance, improve battery safety, rate performance, and good stability of the electrode sheet structure, and the preparation process is relatively simple, economical and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have been widely studied due to their high energy density, stable operating voltage, light weight and environmental friendliness, and have been successfully applied in many fields such as portable consumer electronics, new energy vehicles and storage systems. The positive electrode material is an important component of lithium-ion batteries and a key factor in determining the performance and cost of lithium-ion batteries.

[0003] According to the different structures, the lithium-ion battery positive electrode materials that are widely studied at present are mainly divided into three categories: ① layered transition metal oxides, such as: high-nickel multi-component composite positive electrode materials (referred to as high-nickel positive electrode materials); ② olivine structure compounds; ③ spinel structure compounds; Among them, high-nickel positive electrode materials have become the main research direction of high-capacity positive electrode materials in recent years due to their excellent overall electrochemical performance. Studies have found that as the nickel content increases, high-nickel cathode materials provide higher specific capacity, but sacrifice capacity retention and interface stability. The resulting problems include: (1) It is difficult for high-nickel cathode materials to achieve high cycle performance while improving energy density; (2) The thermal stability and / or electrochemical stability of high-nickel cathode materials with the electrolyte are poor, posing potential thermal runaway and safety risks; (3) During the cyclic charge and discharge process, the structural stability of high-nickel cathode materials is insufficient, resulting in defects such as microcracks, which affect the service life of the battery; (4) When high-nickel cathode materials are intended to improve energy density and achieve high cycle performance, production is difficult, the process is complicated, and / or expensive metal elements need to be introduced, resulting in a significant increase in cost. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a lithium-ion battery positive electrode sheet and a preparation method thereof, and a lithium-ion battery, so as to solve at least one of the following problems existing in existing lithium-ion batteries: (1) It is difficult for high-nickel positive electrode materials to improve energy density while taking into account high cycle performance; (2) The thermal stability and / or electrochemical stability of high-nickel positive electrode materials with electrolytes are poor, and there are thermal runaway and safety risks; (3) During the charge and discharge process, the high-nickel positive electrode materials have insufficient structural stability and defects such as microcracks, which affect the service life; (4) Although the energy density can be improved and high cycle performance can be taken into account, the production is difficult, the process flow is complicated, and / or expensive metal elements need to be introduced, resulting in a significant increase in cost.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a lithium-ion battery positive electrode sheet, comprising a positive electrode current collector and an active material layer disposed on the positive electrode current collector and containing a modifier; wherein the modifier comprises a polymer electrolyte and an inorganic filler, and the synthetic monomer of the polymer electrolyte comprises a cross-linkable perfluoroalkyl ionic liquid, namely, monomer A, and the number of fluorine atoms in monomer A reaches or exceeds 12.

[0007] Furthermore, the structure of the active material layer containing the modifier is one of the following two situations or a combination of both:

[0008] (1) The modifier is applied directly to the surface of the active material layer as an additional coating, i.e., a secondary coating, and the secondary coating also includes a binder;

[0009] (2) The modifier is mixed with the components of the active material layer as a blending material to form an integrated active material layer.

[0010] Further, for case (1), in terms of mass percentage, the inorganic filler accounts for 5-50wt% of the secondary coating, the polymer electrolyte accounts for 45-90wt% of the secondary coating, and the binder accounts for 5-50wt% of the secondary coating;

[0011] For case (2), the inorganic filler accounts for 5-50 wt % of the modifier, and the polymer electrolyte accounts for 50-95 wt % of the modifier, in terms of mass percentage.

[0012] Further, for case (1), the surface density of the secondary coating is 0.01-5 mg / cm 2 , thickness is 0.05-20μm;

[0013] For case (2), the surface density of the blended material is 0.01-5 mg / cm 2 .

[0014] Furthermore, the porosity of the active material layer containing the modifier is ≤20%; and / or,

[0015] The inorganic filler comprises one or more of an active filler or an inert filler, wherein the active filler comprises Li3PS4, Li7Ge2P5S 10 , Li 1+x Al x Ti 2-x (PO4)3 and Li7La3Zr2O 12 At least one of .

[0016] Furthermore, the synthetic monomers of the polymer electrolyte also include: a nitrile monomer containing a branched structure, namely monomer B, and / or vinylene carbonate, namely monomer C.

[0017] Furthermore, the mass ratio of monomer A:monomer B:monomer C in the synthetic monomers of the polymer electrolyte is (5-10):(1-10):(1-10); and / or,

[0018] The proportion of monomer A in the synthetic monomers of the polymer electrolyte to the total weight of the monomers is 30%-40%.

[0019] Furthermore, the cross-linkable perfluoroalkyl ionic liquid, i.e., monomer A, has a structural formula (1):

[0020] (1)

[0021] In formula (1), X and Y are both imidazoles, and R is selected from a perfluorinated C6-C 10 Alkylene, the chemical formula of R is -C Q F 2Q -, Q is an integer from 6 to 10, Z - and Z' - are all sulfonyl imide ions, wherein the sulfonyl imide ions include one or more sulfonyl imide ions substituted or not substituted by fluorine; and / or,

[0022] The structural formula of the nitrile monomer containing a branched structure, namely monomer B, is formula (2):

[0023] (2)

[0024] In formula (2), R' is a C3-C 10 of branched chain alkylene.

[0025] In a second aspect, the present invention further provides a method for preparing the positive electrode sheet of a lithium ion battery as described above, wherein the preparation method specifically comprises the following steps:

[0026] S1.1: Weigh appropriate amounts of inorganic fillers and binders according to a predetermined ratio, add them to an organic solvent, and ensure that all components are evenly dispersed to form solution A;

[0027] S1.2: Weigh the synthetic monomers and initiator of the polymer electrolyte according to the formula ratio, add them to solution A, ensure that all components are evenly dispersed, and obtain a secondary coating solution;

[0028] S1.3: coating the secondary coating solution on the surface of the active material layer on the positive electrode current collector, and completing the polymerization of the synthetic monomers of the polymer electrolyte by light initiation and / or heat initiation to prepare a lithium ion battery positive electrode sheet with a secondary coating on the active material layer; or,

[0029] The preparation method specifically comprises the following steps:

[0030] S2.1: Weigh an appropriate amount of inorganic filler and the positive electrode active material, conductive agent, and binder contained in the active material layer according to a predetermined ratio, and add them to an organic solvent to ensure that all components are evenly dispersed to form a solution B;

[0031] S2.2: Weigh the synthetic monomers and initiator of the polymer electrolyte according to the formula ratio, add them to solution B, ensure that all components are evenly dispersed, and obtain a positive electrode slurry containing mixed materials;

[0032] S2.3: Coating the positive electrode slurry containing the blended material on the surface of the positive electrode current collector, and completing the polymerization of the synthetic monomers of the polymer electrolyte by light initiation and / or heat initiation to produce a lithium ion battery positive electrode sheet containing the blended material in the active material layer.

[0033] The present invention also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The positive electrode sheet is the lithium-ion battery positive electrode sheet as described in the first aspect or the lithium-ion battery positive electrode sheet obtained by the preparation method as described in the second aspect.

[0034] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0035] (1) One of the innovative points of the present invention is to introduce a polymer electrolyte to modify the positive electrode of a lithium-ion battery. In particular, the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid, which includes at least 12 fluorine atoms. The synergistic effect between functional groups is utilized to help achieve higher energy density while taking into account high cycle stability.

[0036] (2) In the present invention, a polymer electrolyte is introduced to modify the positive electrode of a lithium-ion battery. In particular, the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid, which can stabilize the positive electrode structure, inhibit the exothermic reaction between the positive electrode and the electrolyte, and improve the thermal stability of the positive electrode material, thereby significantly improving the safety of the battery.

[0037] (3) In the present invention, a polymer electrolyte is introduced to modify the positive electrode of a lithium-ion battery, and in particular, the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid, which can significantly improve the rate performance of the battery.

[0038] (4) On the basis of polymer electrolyte, the introduction of inorganic fillers can improve the mechanical properties and structural stability of the active material layer containing the modifier; the addition of inorganic fillers can also reduce the crystallinity of the polymer electrolyte, increase the mobility of the polymer chain segments, help to improve the lithium ion migration number and conductivity, improve the interface compatibility between the polymer electrolyte and the positive electrode active material, and reduce the interface impedance, thereby further improving the battery performance, including rate performance and cycle performance, while ensuring high energy density. The addition of inorganic fillers can also improve the thermal stability and chemical stability of the positive electrode, further improving the safety and service life of the battery.

[0039] (5) In some preferred embodiments, by optimizing the ratio of inorganic filler to polymer electrolyte, the positive effect of the modifier (including inorganic filler and polymer electrolyte) on improving the conductivity, oxidation potential, thermal stability and safety, and interface stability of the positive electrode sheet can be maximized, thereby further improving the overall performance of the battery, including cycle performance, safety performance, service life, and rate performance, while ensuring high energy density.

[0040] (6) In some preferred embodiments, by adopting a preferred surface density and coating thickness, and controlling the porosity of the active material layer containing the modifier within a suitable range, it helps to further improve the overall performance of the battery, including cycle performance, safety performance, service life, and rate performance, while ensuring high energy density.

[0041] (7) In some preferred embodiments, in the copolymerization system of the polymer electrolyte used to modify the positive electrode, a nitrile monomer containing a branched structure and / or vinylene carbonate is further introduced to help further improve the cycle performance, enhance the safety, and improve the rate performance while ensuring high energy density.

[0042] (8) In some preferred embodiments, the performance and safety of the battery can be further improved by carefully designing the ratio between the synthetic monomers of the polymer electrolyte.

[0043] (9) The preparation method provided by the present invention is cost-effective, the process flow is relatively simple and efficient, and the use of expensive metal elements is avoided. By providing a flexible preparation scheme (secondary coating and blending scheme), the compatibility with the existing production process of positive electrode materials is improved, showing great application potential.

[0044] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components;

[0046] Figure 1 The EIS spectra of the positive electrode sheets obtained in the examples and comparative examples of the present invention are shown. DETAILED DESCRIPTION

[0047] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0048] The inventors of the present invention have found that a key factor in the performance degradation of lithium-ion batteries is the side reactions occurring at the internal electrolyte interface. For example, for a high-nickel cathode material system with a nickel content of 0.6 (inclusive) or more, increasing the nickel content can increase the specific capacity to achieve high energy density performance, but the problems it brings include: the increase in nickel content will result in excess Ni 3+ and Ni 4+ , which leads to an increase in side reactions at the interface between high-nickel cathode materials and electrolytes, thus affecting cycle performance, interface stability, and mechanical properties. The specific reasons are: (1) Ni 4+ The appearance of will aggravate the side reaction between the positive electrode and the electrolyte, resulting in the thickening of the CEI film on the surface of the positive electrode material and severe surface phase change, increased impedance, and reduced cycle performance; in addition, during the synthesis of high-nickel positive electrode materials, LiOH impurities will be introduced on the surface of the positive electrode material. The impurities will react with the electrolyte to generate HF, causing the dissolution of metal ions in the positive electrode material, resulting in a decrease in cycle performance; (2) Ni 4+ It has strong oxidizing property and tends to be reduced to Ni 3+ ; During this process, oxygen is released from the surface of the material, which further reacts with the electrolyte and the negative electrode, causing the interface stability between the electrode and the electrolyte to decrease rapidly, which may lead to serious safety issues; (3) Due to the increase of side reactions at the interface between the high-nickel positive electrode material and the electrolyte, the mechanical properties and structural stability of the high-nickel positive electrode material decrease, making it prone to problems such as microcracks and peeling, resulting in a decrease in the battery life.

[0049] In order to improve the above problems, although some researchers have proposed some modification methods in recent years, including surface modification, element doping, single crystal structure and concentration gradient design, however, the existing modification methods still have deficiencies in at least one aspect of achieving high cycle stability of lithium-ion battery positive electrodes, ensuring safety, extending cycle life, simplifying processes and reducing costs, and it is difficult to meet the market's growing demand for lithium-ion battery performance, safety and durability. Therefore, it is particularly urgent to research and develop more effective modification strategies.

[0050] Based on this, in the first aspect, the present invention provides a lithium-ion battery positive electrode sheet, comprising a positive electrode collector and an active material layer disposed on the positive electrode collector and containing a modifier; wherein the modifier comprises a polymer electrolyte and an inorganic filler, and the synthetic monomer of the polymer electrolyte comprises a cross-linkable perfluoroalkyl ionic liquid, namely monomer A, and the number of fluorine atoms in monomer A reaches or exceeds 12.

[0051] In some specific embodiments, the number of fluorine atoms in monomer A is 12 to 40. For example, the number of fluorine atoms is 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38.

[0052] Compared with the prior art, one of the innovations of the present invention is the introduction of a polymer electrolyte to modify the positive electrode of a lithium-ion battery. In particular, the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid, namely, monomer A, which includes at least 12 fluorine atoms. Its special chemical structure helps to achieve higher energy density while taking into account high cycle stability. Specifically, (1) High energy density: the introduction of multiple fluorine atoms can widen the electrochemical window, which means that the battery can withstand higher voltages without electrolyte decomposition, thereby allowing the use of positive electrode materials with higher energy density, thereby improving the energy density of the battery; due to the high polarity of fluorine atoms, the introduction of multiple fluorine atoms can increase the oxidation potential of the electrolyte; in some preferred embodiments, monomer A also contains imidazole groups, which also helps to widen the electrochemical window and increase the oxidation potential, which enables the battery to work stably at higher voltages and helps to develop high energy density batteries; (2) High cycle performance: the introduction of multiple fluorine atoms and the introduction of imidazole groups in some preferred embodiments can not only widen the electrochemical window, but also improve the interface stability between the electrode and the electrolyte. A wider electrochemical window and better interface stability help to reduce side reactions of the battery during the cycle process and reduce capacity decay, thereby improving the cycle stability of the battery and extending the battery life.

[0053] In the present invention, a polymer electrolyte is introduced to modify the positive electrode of a lithium-ion battery, and in particular, the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid, which can stabilize the positive electrode structure, inhibit the exothermic reaction between the positive electrode and the electrolyte, and improve the thermal stability of the positive electrode material, thereby significantly improving the safety of the battery. The bond energy of the CF bond is relatively large, and the thermal stability of the imidazole group included in some preferred embodiments is good, which helps to improve the thermal stability of the battery positive electrode and the electrochemical stability between the positive electrode and the electrolyte, and can effectively reduce the thermal runaway and safety risks of the battery and extend the battery cycle life.

[0054] In the present invention, the positive electrode of the lithium-ion battery is modified by introducing a polymer electrolyte, and in particular, the synthetic monomer of the polymer electrolyte includes a cross-linkable perfluoroalkyl ionic liquid, which can significantly improve the rate performance of the battery. The introduction of fluorine atoms increases the electronegativity, promotes the dissociation of lithium salts, produces more freely moving lithium ions, thereby enhancing the transmission of ions and improving the charge and discharge efficiency, i.e., the rate performance, of the battery; at the same time, the longer perfluoroalkylene group in monomer A can improve the internal structure of the cross-linked polymer, improve the segment creep of the polymer molecule, and thus promote the transmission rate of ions, and has little effect on the oxidation potential, thereby improving the rate performance of the battery without affecting the high energy density and cycle performance of the battery; in some preferred embodiments, monomer A also contains an imidazole group, which, due to its special cyclic structure, acts as an ion transmission site, reduces the migration energy barrier of ions in the polymer electrolyte, improves the mobility of ions, and also helps to improve the rate performance of the battery.

[0055] In the present invention, the addition of inorganic fillers can reduce the crystallinity of the polymer electrolyte and increase the mobility of the polymer chain segments, thereby promoting the conduction of lithium ions. In addition, the interaction between the inorganic filler and the polymer electrolyte at the two-phase interface will provide an additional transmission path for lithium ions, which helps to improve the lithium ion migration number and conductivity. The inorganic filler can also improve the interface compatibility between the polymer electrolyte and the positive electrode active material and reduce the interface impedance, thereby further improving the battery performance, including rate performance and cycle performance, while ensuring high energy density.

[0056] It should be noted that inorganic fillers can also adsorb trace impurities (such as moisture) in the polymer electrolyte to avoid the negative impact of these trace impurities on battery performance; the addition of inorganic fillers can also improve the mechanical properties of the polymer electrolyte, enhance the structural stability of the active material layer containing the modifier, and help the integrity of the battery under mechanical stress, thereby improving the safety and reliability of the battery and its service life; the addition of inorganic fillers can also improve the thermal stability of the active material layer containing the modifier, reduce the performance degradation of the battery under high temperature conditions, and help the battery to work stably in a wider temperature range; the addition of inorganic fillers can also improve the chemical stability of the active material layer containing the modifier, reduce the side reactions of the battery during the charge and discharge process, and improve the cycle performance and service life of the battery.

[0057] In some preferred embodiments, the cross-linkable perfluoroalkyl ionic liquid, i.e., monomer A, has a structural formula (1):

[0058] (1)

[0059] In formula (1), X and Y are both imidazoles, and R is selected from a perfluorinated C6-C 10 Alkylene, the chemical formula of R is -C Q F 2Q -, Q is an integer from 6 to 10, Z - and Z' - All are sulfonyl imide ions.

[0060] Optionally, in formula (1), the sulfonyl imide ion includes one or more sulfonyl imide ions substituted or not substituted by fluorine. Preferably, the sulfonyl imide ion includes one or more sulfonyl imide ions substituted by fluorine. Further preferably, the sulfonyl imide ion substituted by fluorine includes: di(trifluoromethylsulfonyl)imide anion (TFSI for short) - ), bis(fluorosulfonyl)imide anion (FSI for short) - ) or both.

[0061] In some preferred embodiments, the synthetic monomers of the polymer electrolyte further include: a nitrile monomer containing a branched structure, namely, monomer B, and / or vinylene carbonate, namely, monomer C.

[0062] In one specific embodiment, the structural formula of the nitrile monomer containing a branched structure is formula (2):

[0063] (2)

[0064] In formula (2), R' is a C3-C 10 of branched chain alkylene.

[0065] It should be noted that further introducing monomer B (i.e., a nitrile monomer containing a branched structure) and / or monomer C (i.e., vinylene carbonate) into the copolymer system of the polymer electrolyte used to modify the positive electrode can help to further improve the cycle performance, enhance safety, and improve the rate performance while ensuring high energy density. Specifically, (1) Monomer B: In the copolymerization system, by adding a nitrile monomer containing a branched structure and an ester group, the creep of the polymer molecular chain segments can be increased, and the ionic conductivity of the polymer electrolyte can be improved. In addition, the nitrile structure can synergize with fluorine to further promote the transmission of lithium ions. The polymer electrolyte containing nitrile groups has a wide electrochemical stability window and can effectively inhibit the dissolution of transition metals. At the same time, the flame retardant properties of the copolymerized nitrile group help to improve the thermal stability of the battery, thereby improving the energy density of the battery, improving the cycle performance and increasing safety; (2) Monomer C: In the copolymerization system, by introducing vinyl carbonate monomers for polymerization, the free volume of the polymer chain can be increased, thereby increasing the migration rate of lithium ions, enhancing the ionic conductivity, and thus improving the battery rate performance; the introduction of vinyl carbonate monomers can also help to increase the oxidation potential and reduce the side reactions between the positive electrode and the electrolyte. In addition, when vinyl carbonate monomers are copolymerized with monomer A or "monomer A + monomer B", the synergistic effect between the functional groups can be better exerted, which helps to improve the energy density of the battery, improve the cycle performance, increase safety, and extend the service life of the battery.

[0066] In some preferred embodiments, the mass ratio of monomer A:monomer B:monomer C in the synthetic monomers of the polymer electrolyte is (5-10):(1-10):(1-10); and / or,

[0067] The proportion of monomer A in the synthetic monomers of the polymer electrolyte to the total weight of the monomers is 30%-40%.

[0068] In the synthesis of polymer electrolytes, the performance and safety of the battery can be further improved by carefully designing the ratio of monomers. Specifically, the mass ratio of monomer A, monomer B and monomer C is (5-10): (1-10): (1-10), and / or the proportion of monomer A to the total mass of monomers is 30%-40%. Such a ratio relationship helps to better play the synergistic effect between the monomers, and can maximize the positive effects of polymer electrolytes on improving conductivity, increasing oxidation potential and widening electrochemical window, increasing thermal stability and safety, and interfacial stability, thereby improving the overall performance of the battery, including cycle performance, safety performance, service life, and rate performance, while ensuring high energy density.

[0069] More preferably, the mass ratio of monomer A:monomer B:monomer C in the synthetic monomers of the polymer electrolyte is 10:(6-8):(9-10).

[0070] In a specific embodiment, the synthesis process of the monomer A mainly includes the following steps:

[0071] (a) In a first solvent, monomer I, monomer II and monomer III are stirred and refluxed at 60-90° C. for 24-72 hours, and after stirring, cooled to room temperature, washed, and subjected to reduced pressure distillation to obtain a cross-linkable perfluoroalkyl prepolymer solution;

[0072] Wherein, monomer I and monomer III are both vinyl imidazole monomers, and their chemical structures both contain an imidazole ring and a vinyl group; the chemical formula of monomer II is MRM, where M is a halogen, and R is selected from a perfluorinated C6-C 10 Alkylene;

[0073] (b) In a second solvent, the cross-linkable perfluoroalkyl prepolymer solution of step (a) and the alkali metal salt containing a sulfonyl imide group are stirred for 2-24 hours, and after the stirring is completed, the solution is washed to obtain a cross-linkable perfluoroalkyl ionic liquid after ion exchange.

[0074] Illustratively, the first solvent is ethyl acetate, and the second solvent is deionized water.

[0075] In a specific embodiment, the structural formula of the polymer electrolyte obtained by copolymerization of monomer A, monomer B, and monomer C is formula (3):

[0076] (3)

[0077] In formula (3), m and m' are each independently an integer of 100 to 5000, n and n' are each independently an integer of 0 to 1000, and y and y' are each independently an integer of 0 to 1000.

[0078] By controlling the ratio of the three monomers to form a polymer electrolyte with an appropriate number of repeating units, the synergistic effect of the functional groups in the polymer electrolyte (for example, fluorine atoms, imidazole groups, and nitrile groups) can be better exerted, maximizing the positive effect of the polymer electrolyte on improving conductivity, oxidation potential, thermal stability, safety, and interface stability, thereby improving the overall performance of the battery, including cycle performance, safety performance, service life, and rate performance, while ensuring high energy density.

[0079] Illustratively, m and m' are each independently 500, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500; n and n' are each independently 100, 200, 500, 800; y and y' are each independently 100, 200, 500, 800.

[0080] Optionally, the structure of the active material layer containing the modifier is one of the following two situations or a combination of both:

[0081] (1) The modifier is applied directly to the surface of the active material layer as an additional coating, i.e., a secondary coating, and the secondary coating also includes a binder;

[0082] (2) The modifier is mixed with the components of the active material layer as a blending material to form an integrated active material layer.

[0083] It can be understood that, for the positive electrode sheet of the present invention, providing two different active material layer modification schemes can enhance its flexibility and adaptability in various application scenarios.

[0084] Preferably, for situation (1), in terms of mass percentage, the inorganic filler accounts for 5-50wt% of the secondary coating, the polymer electrolyte accounts for 45-90wt% of the secondary coating, and the binder accounts for 5-50wt% of the secondary coating.

[0085] Preferably, for situation (2), in terms of mass percentage, the inorganic filler accounts for 5-50wt% of the modifier, and the polymer electrolyte accounts for 50-95wt% of the modifier.

[0086] By optimizing the ratio of inorganic fillers to polymer electrolytes, the positive effect of modifiers (including inorganic fillers and polymer electrolytes) on improving the conductivity, oxidation potential, thermal stability and safety, and interface stability of the positive electrode can be maximized, thereby further improving the overall performance of the battery, including cycle performance, safety performance, service life, and rate performance, while ensuring high energy density.

[0087] Further preferably, for situation (1), the inorganic filler accounts for 15%-25wt% of the secondary coating; the polymer electrolyte accounts for 60-80wt% of the secondary coating; and the binder accounts for 5-15wt% of the secondary coating.

[0088] Further preferably, for situation (2), the inorganic filler accounts for 15%-30wt% of the modifier; and the polymer electrolyte accounts for 70-85wt% of the modifier.

[0089] It is understood that in the present invention, the surface density refers to the total mass per unit area of ​​each component of the modifier, namely the polymer electrolyte and the inorganic filler. The surface density can be controlled by adjusting the slurry formula, coating thickness and post-coating treatment process.

[0090] Preferably, for case (1), the surface density of the secondary coating is 0.01-5 mg / cm 2, with a thickness of 0.05-20 μm. More preferably, the surface density of the secondary coating is 0.1-2 mg / cm 2 , thickness is 0.1-10μm.

[0091] Preferably, for case (2), the surface density of the mixed material is 0.01-5 mg / cm 2 More preferably, the surface density of the blended material is 0.1-2 mg / cm 2 .

[0092] It should be noted that the use of the above-mentioned preferred surface density and coating thickness (for the secondary coating) helps to further improve the overall performance of the battery, including cycle performance, safety performance, service life, and rate performance, while ensuring high energy density; if the surface density of the modifier is too small or the thickness of the secondary coating is too thin, the improvement in the porosity of the active material layer is small, and the ideal physical barrier protection effect cannot be achieved, affecting the safety performance and service life; if the surface density is too large or the thickness of the secondary coating is too large, the battery energy density is affected, and the ionic conductivity of the positive electrode sheet will be reduced, affecting the cycle performance and rate performance.

[0093] For example, for case (1) or (2), the surface density may be 0.25 mg / cm 2 , 0.5mg / cm 2 , 0.75mg / cm 2 、1.00mg / cm 2 , 1.25mg / cm 2 , 1.5mg / cm 2 、1.75mg / cm 2 .

[0094] Exemplarily, for case (1), the thickness may be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm.

[0095] It is understood that the porosity of a battery electrode generally refers to the proportion of the pore space in the electrode, usually expressed as a percentage. Specifically, the porosity mentioned in the present invention refers to the porosity of the integrated active material layer including the secondary coating obtained after the secondary coating is applied to the surface of the positive electrode active material layer, or the porosity of the integrated active material layer mixed with a polymer electrolyte and an inorganic filler. The porosity can be controlled by adjusting the material properties (for example: the type and properties of polymer electrolytes, inorganic fillers, active materials, conductive agents, adhesives), slurry formulations, coating processes, and post-coating treatment processes.

[0096] Preferably, the porosity of the active material layer containing the modifier is ≤20%; further preferably, 3%≤ ≤20%; more preferably, 5%≤ ≤15%.

[0097] For example, the porosity It can be 7%, 9%, 11%, or 13%.

[0098] It should be noted that the use of the above-mentioned appropriate porosity can achieve the optimal balance between the protective effect of the modifier on the battery and the battery performance. If the porosity is too large, the protective effect of the modifier will be affected, and an effective physical protective barrier cannot be formed on the surface of the active material, making it difficult to effectively reduce the side reactions between the positive electrode and the electrolyte, which is not conducive to improving battery performance. Furthermore, controlling the porosity at 3% or above can ensure the normal penetration of the electrolyte and the transmission of lithium ions while achieving effective protection, thereby ensuring the high cycle and rate performance of the battery.

[0099] Optionally, the inorganic filler comprises one or more of an active filler or an inert filler, wherein the active filler comprises Li3PS4, Li7Ge2P5S 10 , Li 1+x Al x Ti 2-x (PO4)3 and Li7La3Zr2O 12 Preferably, Li 1+ x Al x Ti 2-x (PO4)3, 0≤x≤0.5; illustratively, x=0.3, 0.4. Preferably, the inorganic filler is an active filler containing lithium, which can be used as a solid electrolyte. After being compounded with a polymer electrolyte, it can significantly improve the ionic conductivity of the polymer electrolyte, thereby improving the ionic conductivity of the active material layer containing the modifier. At the same time, the use of active fillers also helps to further broaden the electrochemical window to further improve the battery performance, including rate performance, energy density, and cycle performance.

[0100] Specifically, the inert filler is mainly an inorganic material that does not contain lithium, including but not limited to oxides, fluorides, and nitrides; illustratively, one or a combination of SiO2, Al2O3, TiO2, AlF3, FeF3, Co3Mo3N, and BaTiO3.

[0101] In a second aspect, the present invention also provides a method for preparing the positive electrode sheet of a lithium-ion battery as described above.

[0102] The preparation method specifically comprises the following steps:

[0103] S1.1: Weigh appropriate amounts of inorganic fillers and binders according to a predetermined ratio, add them to an organic solvent, and ensure that all components are evenly dispersed to form solution A;

[0104] S1.2: Weigh the synthetic monomers and initiator of the polymer electrolyte according to the formula ratio, add them to solution A, ensure that all components are evenly dispersed, and obtain a secondary coating solution;

[0105] S1.3: coating the secondary coating solution on the surface of the active material layer on the positive electrode current collector, and completing the polymerization of the synthetic monomers of the polymer electrolyte by light initiation and / or heat initiation to prepare a lithium ion battery positive electrode sheet with a secondary coating on the active material layer; or,

[0106] The preparation method specifically comprises the following steps:

[0107] S2.1: Weigh an appropriate amount of inorganic filler and the positive electrode active material, conductive agent, and binder contained in the active material layer according to a predetermined ratio, and add them to an organic solvent to ensure that all components are evenly dispersed to form a solution B;

[0108] S2.2: Weigh the synthetic monomers and initiator of the polymer electrolyte according to the formula ratio, add them to solution B, ensure that all components are evenly dispersed, and obtain a positive electrode slurry containing mixed materials;

[0109] S2.3: Coating the positive electrode slurry containing the blended material on the surface of the positive electrode current collector, and completing the polymerization of the synthetic monomers of the polymer electrolyte by light initiation and / or heat initiation to produce a lithium ion battery positive electrode sheet containing the blended material in the active material layer.

[0110] Illustratively, the synthetic monomers of the polymer electrolyte include at least monomer A, and further, may include at least one of monomer B and monomer C.

[0111] In some preferred embodiments, for the light-initiated method, following step S1.3 or S2.3, the positive electrode sheet after the light-initiated polymerization is subjected to heat treatment to further promote complete curing and ensure complete volatilization of the organic solvent, thereby improving the mechanical structural stability of the active material layer containing the modifier. Preferably, the temperature of the heat treatment of the positive electrode sheet after the light-initiated polymerization is 80-120°C, and the heating treatment time is 8h-12h. Exemplarily, the heating treatment temperature is 90°C, 100°C, 110°C, and the heating treatment time is 11h, 10h, 9h.

[0112] Optionally, in step S1.3 or S2.3, for the thermal initiation method, the heating temperature of thermal polymerization is 50-110°C, and the heating time is 30min-48h; preferably, the heating temperature of thermal polymerization is 70-90°C, and the heating time is 10h-20h. Exemplarily, the heating temperature is 75°C, 80°C, 85°C; the heating time is 18h, 16h, 14h, 12h.

[0113] Optionally, in step S1.3 or S2.3, for the light initiation method, the illumination wavelength of photopolymerization is 100nm-900nm, and the illumination time is 10s-2h; preferably, the illumination wavelength is 200nm-420nm; and the illumination time is 10s-1h.

[0114] Exemplarily, the illumination wavelength is 250nm, 300nm, 365nm, 395nm, 405nm; the illumination time is 50min, 40min, 20min, 10min, 5min, 1min, 30s.

[0115] More preferably, the illumination wavelength is 350nm-420nm; and the illumination time is 20s-40s.

[0116] Preferably, in step S1.3 or S2.3, the coating method includes but is not limited to at least one of blade coating, wire rod coating, and gravure coater coating.

[0117] In the present invention, the initiator includes a thermal initiator and a photoinitiator; preferably, the thermal initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, dialkyl peroxide, potassium persulfate, isopropylbenzene hydroperoxide, and tert-butyl hydroperoxide; the photoinitiator includes at least one of 2-hydroxy-methylphenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0118] Preferably, the amount of the initiator added is 0.1wt%~5wt% of the total mass of the monomers; more preferably, the amount of the initiator added is 0.5wt%~1.5wt% of the total mass of the monomers; illustratively, the amount of the initiator added is 0.8wt%, 1.0wt%, 1.2wt% of the total mass of the monomers.

[0119] In the present invention, the binder includes but is not limited to at least one of polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile, polyvinyl alcohol, polypropylene oxide, polyether, polyphosphazene, polycarbonate, vinylidene fluoride-hexafluoropropylene copolymer, nitrile rubber or polyvinyl chloride.

[0120] In the present invention, the organic solvent includes but is not limited to at least one of N,N-dimethylformamide (DMF), methyl pyrrolidone (NMP), and acetone. In addition, other organic solvents with strong volatility that can ensure uniform dispersion of various components added to the solvent can also be selected.

[0121] In a third aspect, the present invention further provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an isolation membrane separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the positive electrode sheet is the lithium-ion battery positive electrode sheet as described in the first aspect or the lithium-ion battery positive electrode sheet obtained by the preparation method as described in the second aspect.

[0122] The present invention also provides the use of the lithium-ion battery positive electrode sheet as described above in electrical equipment. The electrical equipment includes terminal consumer products and large-scale electrical equipment. The terminal consumer products include but are not limited to commonly used 3C products, for example, computers, mice, mobile phones, digital cameras, digital audio players, smart watches, radios, and Bluetooth headsets. The large-scale electrical equipment includes but is not limited to electrical equipment for transportation.

[0123] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and comparative examples.

[0124] Example 1

[0125] This embodiment provides a method for preparing a positive electrode sheet of a lithium ion battery, comprising the following steps:

[0126] S1.0, preparation of cross-linkable perfluoroalkyl ionic liquid:

[0127] 100 g of 1-vinylimidazole, 650 g of 1,8-dibromohexafluorooctane and 500 g of ethyl acetate were added to a reactor and stirred at 90°C for 24 h. After stirring, the mixture was cooled to room temperature, washed three times with 50 mL of ethyl acetate, and distilled under reduced pressure to obtain a cross-linkable perfluoroalkyl prepolymer liquid. 100 g of the above-obtained prepolymer liquid and 66 g of lithium bis(trifluoromethanesulfonyl)imide (referred to as LiTFSI) were dissolved in 200 mL of deionized water, stirred at room temperature for 2 h, and washed three times with 50 mL of deionized water to obtain a cross-linkable perfluoroalkyl ionic liquid after ion exchange, i.e., monomer A.

[0128] S1.1, add 1.5g BaTiO3 and 1.0g polyvinylidene fluoride (PVDF) to 40.3g N-methylpyrrolidone (NMP), stir at room temperature for 4h to ensure that BaTiO3 and PVDF are evenly dispersed in the NMP solution to form solution A;

[0129] S1.2, weigh 7.5g monomer A and 0.075g azobisisobutyronitrile (AIBN), add them to solution A, and continue stirring at room temperature for 2h to ensure that all components are evenly dispersed to obtain a secondary coating solution;

[0130] S1.3, weigh 8g LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), 1g conductive carbon black (Super P), and 1g PVDF were added to 12.2g NMP solvent and stirred evenly to obtain a slurry with a mass ratio of NCM811: Super P: PVDF of 8:1:1. The slurry was coated on aluminum foil to obtain an NCM811 positive electrode sheet; the secondary coating solution was coated on the surface of the NCM811 positive electrode sheet by a scraper, and the sheet was placed in an oven and heated at 80°C for 18h to complete the polymerization of the monomers to prepare a lithium ion battery positive electrode sheet with a secondary coating on the active material layer. The thickness of the secondary coating was 0.56μm and the surface density was 0.062mg / cm 2 .

[0131] Example 2

[0132] The difference between this embodiment and embodiment 1 is that in step S1.2, 6.25 g of monomer A, 1.25 g of 1-cyanoallyl acetate (monomer B) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0133] Example 3

[0134] The difference between this embodiment and embodiment 1 is that in step S1.2, 6.25 g of monomer A, 1.25 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0135] Example 4

[0136] The difference between this embodiment and embodiment 1 is that in step S1.2, 5.36 g of monomer A, 1.07 g of 1-cyanoallyl acetate (monomer B), 1.07 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0137] Example 5

[0138] The difference between this embodiment and embodiment 1 is that in step S1.2, 6.25 g of monomer A, 0.625 g of 1-cyanoallyl acetate (monomer B), 0.625 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0139] Example 6

[0140] The difference between this embodiment and embodiment 1 is that in step S1.2, 3.57 g of monomer A, 0.36 g of 1-cyanoallyl acetate (monomer B), 3.57 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0141] Example 7

[0142] The difference between this embodiment and embodiment 1 is that in step S1.2, 3.57 g of monomer A, 3.57 g of 1-cyanoallyl acetate (monomer B), 0.36 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0143] Example 8

[0144] The difference between this embodiment and embodiment 1 is that in step S1.2, 2.35 g of monomer A, 0.47 g of 1-cyanoallyl acetate (monomer B), 4.68 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0145] Example 9

[0146] The difference between this embodiment and embodiment 1 is that in step S1.2, 2.35 g of monomer A, 4.68 g of 1-cyanoallyl acetate (monomer B), 0.47 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0147] Example 10

[0148] The difference between this embodiment and embodiment 1 is that in step S1.2, 2.5 g of monomer A, 2.5 g of 1-cyanoallyl acetate (monomer B), 2.5 g of vinylene carbonate (monomer C) and 0.075 g of AIBN are weighed and added to solution A. The remaining steps and parameters are similar to those in embodiment 1.

[0149] Embodiment 11

[0150] The difference between this embodiment and embodiment 1 is that: in step S1.1, 1.0 g of polyvinylidene fluoride (PVDF) and 1.5 g of Li3PS4 are added to 40.3 g of N-methylpyrrolidone (NMP), and stirred at room temperature for 4 h to ensure that Li3PS4 and PVDF are evenly dispersed in the NMP solution to form solution A;

[0151] In step S1.2, 3.0 g of monomer A, 1.8 g of 1-cyanoallyl acetate (monomer B), 2.7 g of vinylene carbonate (monomer C) and 0.075 g of AIBN were weighed and added to solution A. The remaining steps and parameters were similar to those in Example 1.

[0152] Example 12

[0153] The difference between this embodiment and embodiment 1 is that: in step S1.1, 1.0 g of polyvinylidene fluoride (PVDF) and 2.5 g of Li3PS4 are added to 40.3 g of N-methylpyrrolidone (NMP), and stirred at room temperature for 4 h to ensure that Li3PS4 and PVDF are evenly dispersed in the NMP solution to form solution A;

[0154] In step S1.2, 2.6 g of monomer A, 1.56 g of 1-cyanoallyl acetate (monomer B), 2.34 g of vinylene carbonate (monomer C) and 0.065 g of AIBN were weighed and added to solution A. The remaining steps and parameters were similar to those in Example 1.

[0155] Example 13

[0156] The difference between this embodiment and embodiment 1 is that: in step S1.1, 1.0 g of polyvinylidene fluoride (PVDF) and 5.0 g of Li3PS4 are added to 40.3 g of N-methylpyrrolidone (NMP), and stirred at room temperature for 4 h to ensure that Li3PS4 and PVDF are evenly dispersed in the NMP solution to form solution A;

[0157] In step S1.2, 1.6 g of monomer A, 0.96 g of 1-cyanoallyl acetate (monomer B), 1.44 g of vinylene carbonate (monomer C) and 0.04 g of AIBN were weighed and added to solution A. The remaining steps and parameters were similar to those in Example 1.

[0158] Embodiment 14

[0159] The difference between this embodiment and embodiment 1 is that: in step S1.1, 1.0 g of polyvinylidene fluoride (PVDF) and 0.5 g of Li3PS4 are added to 40.3 g of N-methylpyrrolidone (NMP), and stirred at room temperature for 4 h to ensure that Li3PS4 and PVDF are evenly dispersed in the NMP solution to form solution A;

[0160] In step S1.2, 3.4 g of monomer A, 2.04 g of 1-cyanoallyl acetate (monomer B), 3.06 g of vinylene carbonate (monomer C) and 0.085 g of AIBN were weighed and added to solution A. The remaining steps and parameters were similar to those in Example 1.

[0161] Embodiment 15

[0162] The difference between this embodiment and embodiment 11 is that the thickness of the secondary coating is 1.12 μm and the surface density is 0.146 mg / cm 2 The remaining steps and parameters are similar to those in Example 11.

[0163] Example 16

[0164] The difference between this embodiment and embodiment 11 is that the thickness of the secondary coating is 3.46 μm and the surface density is 0.389 mg / cm 2 The remaining steps and parameters are similar to those in Example 11.

[0165] Embodiment 17

[0166] The difference between this embodiment and embodiment 11 is that the thickness of the secondary coating is 10.58 μm and the surface density is 1.434 mg / cm 2 The remaining steps and parameters are similar to those in Example 11.

[0167] Embodiment 18

[0168] The difference between this embodiment and embodiment 11 is that: in step S1.2, AIBN is replaced by phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide; in step S1.3, the secondary coating solution is applied to the surface of the NCM811 positive electrode sheet by a scraper, and is placed under a UV lamp with a wavelength of 405 nm for 30 seconds for photoinitiated polymerization, and then the polymerized electrode sheet is placed in an oven and dried at 80°C for 12 hours to prepare a lithium ion battery positive electrode sheet with a secondary coating on the active material layer, the thickness of the secondary coating is 0.49 μm, and the surface density is 0.058 mg / cm 2 The remaining steps and parameters are similar to those in Example 11.

[0169] Embodiment 19

[0170] The difference between this embodiment and embodiment 18 is that the thickness of the secondary coating is 1.37 μm and the surface density is 0.208 mg / cm 2 The remaining steps and parameters are similar to those in Example 18.

[0171] Embodiment 20

[0172] The difference between this embodiment and embodiment 18 is that the thickness of the secondary coating is 3.89 μm and the surface density is 0.497 mg / cm 2 The remaining steps and parameters are similar to those in Example 18.

[0173] Embodiment 21

[0174] The difference between this embodiment and embodiment 18 is that the thickness of the secondary coating is 11.35 μm and the surface density is 1.577 mg / cm 2 The remaining steps and parameters are similar to those in Example 18.

[0175] Embodiment 22

[0176] This embodiment provides a method for preparing a positive electrode sheet of a lithium ion battery, comprising the following steps:

[0177] S2.0: 100 g of 1-vinylimidazole, 650 g of 1,8-dibromohexafluorooctane and 500 g of ethyl acetate were added to a reactor and stirred at 90°C for 24 h. After stirring, the mixture was cooled to room temperature, washed three times with 50 mL of ethyl acetate and distilled under reduced pressure to obtain a cross-linkable perfluoroalkyl prepolymer liquid. 100 g of the prepolymer obtained above and 66 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI for short) were dissolved in 200 mL of deionized water. After stirring at room temperature for 2 h, the mixture was washed three times with 50 mL of deionized water to obtain a cross-linkable perfluoroalkyl ionic liquid after ion exchange, i.e., monomer A.

[0178] S2.1: Weigh 0.2gLi 1+x Al x Ti2-x (PO4)3, x=0.3 and the active material layer containing 8g NCM811, 1g Super P, and 1g PVDF were added to 13.4g NMP solvent to ensure that all components were evenly dispersed to form solution B;

[0179] S2.2: Weigh 0.32 g of monomer A, 0.19 g of 1-cyanoallyl acetate (monomer B), 0.29 g of vinylene carbonate (monomer C) and 0.008 g of AIBN, and add them to solution B to ensure that all components are evenly dispersed to obtain a positive electrode slurry containing mixed materials;

[0180] S2.3: The positive electrode slurry containing the mixed material is coated on the surface of the aluminum foil, and the monomer A, monomer B and monomer C are polymerized by thermal initiation to prepare a lithium ion battery positive electrode sheet containing the mixed material in the active material layer; the surface density of the mixed material (i.e., polymer electrolyte + inorganic filler) in the positive electrode sheet is 0.793 mg / cm 2 .

[0181] Comparative Example 1

[0182] This comparative example provides a lithium-ion battery positive electrode sheet, and the preparation method of the positive electrode sheet mainly includes the following steps: weighing 8g NCM811, 1g Super P, and 1g PVDF, adding them to 12.2g NMP solvent, stirring evenly to obtain a slurry with a mass ratio of NCM811:SuperP:PVDF of 8:1:1, and coating the slurry on aluminum foil to obtain an NCM811 positive electrode sheet.

[0183] Comparative Example 1-1: It is a test example of the NCM811 positive electrode sheet obtained in the above-mentioned Comparative Example 1, and the test voltage range is 2.5-4.3V.

[0184] Comparative Example 1-2: It is a test example of the NCM811 positive electrode sheet obtained in the above-mentioned Comparative Example 1, and the test voltage range is 2.5-4.4V.

[0185] Performance Testing:

[0186] (a) Cycle performance test: The positive electrode sheets of Examples 1-22 and Comparative Example 1 were used as the positive electrode, a 25 μm thick PP separator was used, and a 0.6 mm thick lithium metal was used as the negative electrode. An electrolyte (1 mol / L LiPF6 EC:DMC:EMC=1:1:1) was added. In this electrolyte formula, EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) were mixed in a volume ratio of 1:1:1 to assemble NCM-lithium metal button cells. The battery long cycle charge and discharge test was carried out at 0.5C.

[0187] (b) DSC test: The positive electrode sheets of Examples 1-22 and Comparative Example 1 were used as the positive electrode, respectively, a 25 μm thick PP separator was used, and a 0.6 mm thick lithium metal was used as the negative electrode. An electrolyte (1 mol / L LiPF6 EC: DMC: EMC = 1:1:1) was added to assemble the NCM-lithium metal button cell. The battery was disassembled after being fully charged at 0.1C, and the disassembled positive electrode sheet was soaked in the DMC solution, left to stand at 80°C for 1h to dry, and the DSC was tested by scraping powder. The DSC test conditions were room temperature to 350°C, the heating rate was 10°C / min, the powder was weighed 8 to 10 mg, 4 μL of electrolyte was added, and the powder was spread all over the bottom of the high-pressure crucible and compacted.

[0188] (c) Electrochemical impedance spectroscopy (EIS) test: The test was performed using a CHI660E electrochemical workstation with a frequency range of 0.001-10 kHz and fitted using Zview software to obtain Figure 1 The results shown, Figure 1 In the figure, the abscissa is the real part of the impedance (Z') and the ordinate is the imaginary part of the impedance (Z'').

[0189] In the above tests (a)-(c), the voltage range in the relevant battery performance tests of Examples 1-5 and Comparative Example 1-1 is 2.5-4.3V, and the voltage range in the relevant battery performance tests of Examples 6-22 and Comparative Example 1-2 is 2.5-4.4V.

[0190] Table 1: The parameters of the lithium-ion battery positive electrode product obtained in the above embodiment are as follows:

[0191]

[0192] Table 2: Performance test conditions and results of examples and comparative examples

[0193]

[0194] Result analysis:

[0195] (a) Analysis of cycle performance test results to evaluate battery performance

[0196] It can be understood that the higher the first efficiency and the capacity retention rate after 200 cycles at 0.5C, the better the battery's cycle performance; among them, the first efficiency: that is, the first efficiency, refers to the ratio of the discharge capacity to the charging capacity of the battery in the first charge and discharge cycle. This indicator reflects the efficiency of the battery when it is used for the first time. The higher the first efficiency, the less power the battery loses during the first charge and discharge process. Capacity retention rate after 200 cycles at 0.5C: This indicator refers to the ratio of the remaining capacity to the initial capacity after the battery has been cycled 200 times at a charge and discharge rate of 0.5C. It is an important indicator for measuring the battery's cycle stability and long-term reliability. The higher the above two indicators are, the better the chemical stability of the positive electrode and its relationship with the electrolyte, and the structural stability of the positive electrode.

[0197] It can be understood that the first-cycle discharge specific capacity usually refers to the amount of electricity that the battery can release during the first discharge process. This indicator can provide an important reference for the energy density of the battery.

[0198] It can be seen from Table 2 that compared with Comparative Examples 1-1 or 1-2 without adding a modifier, under the same voltage conditions, the embodiments of the present invention can obtain higher first efficiency and 200-cycle capacity retention rate and first-cycle discharge specific capacity by modifying the active material layer in the positive electrode by introducing a modifier comprising a polymer electrolyte and an inorganic filler. This shows that the embodiments of the present invention can achieve higher energy density while taking into account high cycle stability.

[0199] Furthermore, compared with Example 1, the overall cycle performance data of Examples 2-5 are better, which shows that in the copolymer system of the polymer electrolyte used to modify the positive electrode, further introducing nitrile monomers and / or vinylene carbonate containing a branched structure can help to further improve the cycle performance while ensuring high energy density.

[0200] It can be seen from Examples 6-22 that the battery electrode provided by the present invention can stably operate at a higher operating voltage (2.5-4.4V), which can not only achieve a higher energy density but also maintain excellent cycle performance.

[0201] Furthermore, compared with Examples 13 and 14, Examples 11 and 12 achieved higher first efficiency and 200-cycle capacity retention rate and first-cycle discharge specific capacity, which shows that by optimizing the ratio of inorganic filler to polymer electrolyte, it helps to further improve the cycle performance of the battery while ensuring high energy density.

[0202] Furthermore, compared with Examples 11 and 17, Examples 15 and 16 achieved higher first efficiency and 200-cycle capacity retention rates and first-cycle discharge specific capacity, and compared with Examples 18 and 21, Examples 19 and 20 achieved higher first efficiency and 200-cycle capacity retention rates and first-cycle discharge specific capacity, which shows that by adopting the preferred surface density and coating thickness, it helps to further improve the cycle performance of the battery while ensuring high energy density.

[0203] (b) DSC result analysis to evaluate safety

[0204] It can be understood that the exothermic peak and exothermic area in the DSC test are important parameters for evaluating the thermal stability and safety of positive electrode materials for lithium-ion batteries. Among them, exothermic peak: On the DSC curve, the exothermic peak usually indicates the highest temperature when the material undergoes an exothermic reaction. This temperature can be used as an important parameter for evaluating the thermal stability of the material. For the positive electrode materials of lithium-ion batteries, the exothermic peak can indicate the risk that the material may begin to decompose or react adversely with the electrolyte at a specific temperature. Exothermic area: The exothermic area on the DSC curve (i.e., the area under the reaction peak) is proportional to the amount of heat released or absorbed by the material in the thermal reaction. This parameter can be used to quantitatively analyze the amount of energy that the material may release in the case of thermal runaway, thereby evaluating its thermal safety. Therefore, the higher the exothermic peak and the smaller the exothermic area, the better the thermal stability and safety of the electrode material.

[0205] It can be seen from Table 2 that, compared with Comparative Examples 1-1 or 1-2 without adding a modifier, the embodiments of the present invention can obtain a higher DSC exothermic peak and a smaller DSC exothermic area by introducing a modifier comprising a polymer electrolyte and an inorganic filler to modify the active material layer in the positive electrode, which shows that the embodiments of the present invention can enable the battery to achieve better thermal stability and improve safety.

[0206] Compared with Examples 6 and 7, Examples 8-10 obtain higher exothermic peaks and smaller exothermic areas, which indicates that when the mass ratio of monomer A, monomer B and monomer C meets the condition of (5-10):(1-10):(1-10), further satisfying that the proportion of monomer A in the total mass of monomers is 30%-40%, it helps to further improve thermal stability and safety.

[0207] Furthermore, compared with Examples 13 and 14, Examples 11 and 12 obtained higher exothermic peaks and smaller exothermic areas, which shows that optimizing the ratio of inorganic fillers to polymer electrolytes can help further improve thermal stability and safety.

[0208] Furthermore, compared with Examples 11 and 17, Examples 15 and 16 obtain higher exothermic peaks and smaller exothermic areas; compared with Examples 18 and 21, Examples 19 and 20 obtain higher exothermic peaks and smaller exothermic areas; this indicates that by adopting the preferred surface density and coating thickness, it helps to further improve thermal stability and safety.

[0209] (c) Analysis of EIS test results to evaluate rate performance

[0210] from Figure 1 It can be seen that compared with comparative example 1-1, embodiments 1, 2 and 4 have lower charge transfer impedance (Rct) values ​​and smaller diffusion impedance slopes, which indicates that the embodiments of the present invention can significantly improve the rate performance of the battery; among them, the rate performance of embodiment 4 is better than that of embodiment 2, and the rate performance of embodiment 2 is better than that of embodiment 1, which indicates that in the synthetic monomers of the polymer electrolyte, the present invention further introduces monomers B and C for copolymerization on the basis of monomer A, which helps to further improve the rate performance.

[0211] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A positive electrode sheet for a lithium-ion battery, characterized in that: The invention comprises a positive electrode current collector and an active material layer disposed on the positive electrode current collector and containing a modifier; wherein the modifier comprises a polymer electrolyte and an inorganic filler; The structural formula of the polymer electrolyte is formula (3): (3) In formula (3), m and m' are each independently an integer of 100-5000, n and n' are each independently an integer of 0-1000, and y and y' are each independently an integer of 0-1000; The polymer electrolyte is obtained by copolymerizing a cross-linkable perfluoroalkyl ionic liquid, namely a monomer A, a nitrile monomer containing a branched structure, namely a monomer B, and vinylene carbonate, namely a monomer C; the number of fluorine atoms in the monomer A reaches or exceeds 12; The cross-linkable perfluoroalkyl ionic liquid, i.e., monomer A, has the structural formula (1): (1) In formula (1), X and Y are both imidazoles, and R is selected from a perfluorinated C6-C 10 Alkylene, the chemical formula of R is -C Q F 2Q -, Q is an integer from 6 to 10, Z - and Z' - All are sulfonimide ions; The sulfonyl imide ions include one or more fluorine-substituted sulfonyl imide ions; the fluorine-substituted sulfonyl imide ions include one or two of di(trifluoromethylsulfonyl)imide anions and bis(fluorosulfonyl)imide anions; The structural formula of the nitrile monomer containing a branched structure, namely monomer B, is formula (2): (2) In formula (2), R' is a C3-C 10 of branched chain alkylene.

2. The lithium-ion battery positive electrode sheet according to claim 1, characterized in that: The structure of the active material layer containing the modifier is one of the following two situations or a combination of both: (1) The modifier is applied directly to the surface of the active material layer as an additional coating, i.e., a secondary coating, and the secondary coating also includes a binder; (2) The modifier is mixed with the components of the active material layer as a blending material to form an integrated active material layer.

3. The lithium-ion battery positive electrode sheet according to claim 2, characterized in that: For case (1), in terms of mass percentage, the inorganic filler accounts for 5-50wt% of the secondary coating, the polymer electrolyte accounts for 45-90wt% of the secondary coating, and the binder accounts for 5-50wt% of the secondary coating; For case (2), in terms of mass percentage, the inorganic filler accounts for 5-50 wt % of the modifier, and the polymer electrolyte accounts for 50-95 wt % of the modifier.

4. The lithium-ion battery positive electrode sheet according to claim 2, characterized in that: For case (1), the surface density of the secondary coating is 0.01-5 mg / cm 2 , thickness is 0.05-20μm; For case (2), the surface density of the blended material is 0.01-5 mg / cm 2 .

5. The lithium-ion battery positive electrode sheet according to claim 1, characterized in that: The porosity of the active material layer containing the modifier is ≤20%; and / or, The inorganic filler comprises one or more of an active filler or an inert filler, wherein the active filler comprises Li3PS4, Li7Ge2P5S 10 , Li 1+x Al x Ti 2-x (PO4)3 and Li7La3Zr2O 12 At least one of .

6. The lithium-ion battery positive electrode sheet according to claim 1, characterized in that: The mass ratio of monomer A:monomer B:monomer C in the synthetic monomers of the polymer electrolyte is (5-10):(1-10):(1-10); and / or, The proportion of monomer A in the synthetic monomers of the polymer electrolyte to the total weight of the monomers is 30%-40%.

7. The method for preparing a positive electrode sheet for a lithium-ion battery according to any one of claims 1 to 6, characterized in that: The preparation method specifically comprises the following steps: S1.1: Weigh appropriate amounts of inorganic fillers and binders according to a predetermined ratio, add them to an organic solvent, and ensure that all components are evenly dispersed to form solution A; S1.2: Weigh the synthetic monomers and initiator of the polymer electrolyte according to the formula ratio, add them to solution A, ensure that all components are evenly dispersed, and obtain a secondary coating solution; S1.3: coating the secondary coating solution on the surface of the active material layer on the positive electrode current collector, and completing the polymerization of the synthetic monomers of the polymer electrolyte by light initiation and / or heat initiation to prepare a lithium ion battery positive electrode sheet with a secondary coating on the active material layer; or, The preparation method specifically comprises the following steps: S2.1: Weigh an appropriate amount of inorganic filler and the positive electrode active material, conductive agent, and binder contained in the active material layer according to a predetermined ratio, and add them to an organic solvent to ensure that all components are evenly dispersed to form a solution B; S2.2: Weigh the synthetic monomers and initiator of the polymer electrolyte according to the formula ratio, add them to solution B, ensure that all components are evenly dispersed, and obtain a positive electrode slurry containing mixed materials; S2.3: Coating the positive electrode slurry containing the blended material on the surface of the positive electrode current collector, and completing the polymerization of the synthetic monomers of the polymer electrolyte by light initiation and / or heat initiation to produce a lithium ion battery positive electrode sheet containing the blended material in the active material layer.

8. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The positive electrode sheet is the positive electrode sheet of a lithium ion battery according to any one of claims 1 to 6 or the positive electrode sheet of a lithium ion battery obtained by the preparation method according to claim 7.

Citation Information

Patent Citations

  • Safety coating, electrode plate, preparation method of electrode plate and lithium ion battery

    CN113488609A

  • Fluorine-containing polymer solid electrolyte coated positive electrode material and preparation method thereof

    CN116130653A

  • Fluorine-containing poly (ethylene carbonate) acrylate-based gel polymer electrolyte as well as preparation and application thereof

    CN117996175A